Reforming the content of teacher professional training in the conditions of European integration - Postryhach, N. (New Collegium, 2023)
The relevance of the study is determined by the public need to transform the content of Ukrainian pedagogical education in the context of its integration into the pan-European scientific and educational space, an effort to get closer to the socio-economic and educational standards of developed OECD member countries, which leads to increased attention of scientists and practitioners to comparative studies of functioning and development of national systems of teacher education in the European region. The solution to the problem of professionalization of teacher training is related to the scientific justification of the content of teacher education in the direction of greater balance of its components: general, special and professional. Despite numerous studies of various aspects of the construction of the content of professional training of future teachers, the problem of reforming its content in the context of European integration remains undeveloped. Therefore, the goals and tasks of the research became the analysis of peculiarities of reforming the content of the teachers’ professional training in the conditions of European integration and the justification of recommendations for improving the content of the training of Ukrainian teachers. Аccording to the results of research by European and ukrainian scientists, the peculiarities of reforming the content of the teachers’ professional training in the conditions of European integration have been clarified: there are noticeable differences between the contexts and features of training programs for the training of junior and senior high school teachers; significant differences regarding the duration of programs in national teacher education systems, which are mostly determined at the macro level and reflect national characteristics of education; debates about whether teacher education should be focused only at the master’s level and precede subject specialization; debatable relation of educational sciences to subject learning in the curriculum of teacher education of the Master of Arts; large-scale transformations of educational programs and institutions of teacher education at the macro level in all countries-universities-partners of EMETT; “square” complexity of the European curriculum of teacher education; the absence of any fast route in European joint master’s programs, which complicates the accreditation procedure in each national context of the respective universities, etc. Recommendations for improving the content of Ukrainian teacher training include taking into account various points of view, subversive relationships between teaching, training, schooling, educational processes, actors and contexts; bridging the gap between theory and practice through integration in curriculum organization and delivery; the professional autonomy of the teacher and the key role of reflective thinking should be the basis of curriculum development and implementation; recognition of accreditation in one national context of the Joint Master’s academic network and its extension to other involved national contexts; strengthening and expanding academic networks for mutual scientific and practical exchanges, etc. The prognostic potential of scientific research is determined by the potential possibility of organizing and implementing further scientific research of a fundamental direction regarding the development of the content of professional training of teachers in Turkey.